Effect of chemotherapy on natural-killer activity and antibody-dependent cell-mediated cytotoxicity in carcinoma of the lung. - Saijo, N. (Nature Publishing Group, 1982)
The effect of chemotherapy on natural killer (NK) activity and antibody-dependent cell-mediated cytotoxicity (ADCC) in 15 advanced carcinomas of the lung was examined with regard to the drug, dose, route and timing of administration. The relationship between the effect of chemotherapy on the prognosis for the patients, and the changes in NK activity and ADCC, was also analysed. The NK activity and ADCC in patients with poor prognosis were significantly subnormal, even before treatment. The NK activity and ADCC began to decrease 2 weeks after the initiation of treatment and reached the lowest level during the 3rd or 4th week in all patients. Thereafter, they returned to the pretreatment level in 8 patients with stabilized disease. In contrast, they were not restored in 7 patients with progressive disease and poor prognosis. In 4 patients it was found that the effect of chemotherapy with pepleomycin and carbazilquinone on NK activity and ADCC differed according to the drug used. From this pilot study it is suggested that NK activity and ADCC are valuable prognostic factors in patients with advanced carcinoma of the lung, and that detailed analysis of the effect of each anticancer agent on NK activity and ADCC is desirable for the establishment of better treatment regimens for advanced carcinoma of the lung.